2021
DOI: 10.1007/s10157-020-02015-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between urine pH and risk of contrast-associated acute kidney injury among patients after emergency percutaneous coronary intervention: a V-shape relationship?

Abstract: Aim We investigated whether perioperative urine pH was associated with contrast-associated acute kidney injury (CA-AKI) in patients undergoing emergency percutaneous coronary intervention (PCI). Methods The study enrolled 1109 consecutive patients undergoing emergency PCI. Patients were divided into three groups based on perioperative urine pH (5.0–6.0, 6.5– 7.0, 7.5–8.5). The primary endpoint was the development of CA-AKI, defined as an absolute increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This study has defined its results based on serum creatinine levels measured 72 hours before the percutaneous coronary intervention and 72 hours after the percutaneous coronary intervention so that the relation of acute kidney injury with this procedure can be established. This study has also revealed that radio-contrast media exposure increases the likelihood of acute kidney injury (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 60%
“…This study has defined its results based on serum creatinine levels measured 72 hours before the percutaneous coronary intervention and 72 hours after the percutaneous coronary intervention so that the relation of acute kidney injury with this procedure can be established. This study has also revealed that radio-contrast media exposure increases the likelihood of acute kidney injury (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 60%